REFORMASI PROMOSI APARATUR SIPIL NEGARA - Muammar Alkadafi; Rusdi Rusdi; Muhammad April (Jurnal Kebijakan Publik, 2018)
Reform of the Promotion of Civil State Apparatus. The position of High Leader (JPT) Pratama is a position that equaled with the structural position of echelon II. b and a. in its filling, the Regional Government of Kabupaten Kampar through the Regional Personnel Board has carried out an open promotion reform of the position on the filling of the Primary Leadership Office. The purpose of this research is to know the promotion of ASN Promotion in the implementation of open selection of filling of Position of High Leader in Kampar Regency Government, and to know the method and activity stages conducted by assessment center of State Islamic University of Sultan Syarif Kasim Riau in selecting competence of candidate of high leadership officer in Pratama Environment of Kampar Regency Government in 2015. The research method used qualitative research with phenomenological approach, qualitative data analysis using Huberman Interactive Model Of Analysis namely; data reduction, data presentation and conclusions. The results of this research can be found in the promotion of ASN in the open selection of high leadership positions in Kampar Regency in 2015, in terms of preparation, implementation and monitoring and evaluation as stipulated in Permanpan-RB Regulation no. 13 Year 2014, procedurally has been implemented in accordance with the provisions. From the result of data analysis of implementation and re- commendation from KASN to the selection implementation process, implicitly it can be concluded that the implementation process contains the principles of objectivity, competitive, transparencyand accountability in every stage process performed by selection committee to 14 (fourteen) selected.